THE DEVELOPMENT OF METHODS FOR MULTILEVEL MODELING AND MANAGEMENT UNDER UNCERTAINTY - Skalozub, V. V.; Razumov, S. Yu.; Skalozub, V. Vl. (Science and Transport Progress, 2008)
The source of inconsistency of data of matrices of pair comparisons, which are utilized in the Analytic Hierarchy Process, is determined. The improved procedure of data processing is developed, which provides more consistent results of pair comparisons and accuracy of solutions of multicriteria problems.